The Factors Affecting of Bed Occupancy Rate (BOR) in Hospital - Mandala, Erlangga Mandala Sakti (PROFESSIONAL HEALTH JOURNAL, 2026)
Background : Bed Occupancy Rate (BOR) is a number that shows the percentage of used shows the percentage of used bed room at certain times in the inpatient unit. This Bed Occupancy Rate (BOR) data can be used to determine the level of utilization of service facilities, find out the quality of hospital services, and find out the level of efficiency of hospital services. Purpose : to find out the factors affecting of Bed Occupancy Rate (BOR) in hospitals. Method : The methods used from literature sources such as Google scholar, pubmed, and research gate. The way to locate literature in a number of key words is, Bed Occupancy Rate (BOR), factors of Bed Occupancy Rate (BOR). Inklational criteria: articles that have titles and content that are relevant to the goal, in Indonesian, English and arabian fulltext, research articles published in 2016-2020. Results : Based on the review of the articles, it is known that factors affecting of Bed Occupancy Rate(BOR) are internal factors such as communication services, the attitude of doctors and nurses, medical assistance, a facility for medical support , human resources and machines and other external factors such as the environment. Conclusion : Of the many factors that affect Bed Occupancy Rate (BOR) in hospitals, the most influential internal factors such as health care procedures and medical support infrastructure are among the most affected Bed Occupancy Rate (BOR) in hospitals.